Addressing Palm Biodiesel as Renewable Fuel for the Indonesian Power Generation Sector: Java-Madura-Bali System - Natarianto Indrawan; Muhammad Ery Wijaya (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2011)
Energy security defined as how to equitably provide available, affordable, reliable efficient, environmentally friendly, proactively governed and socially acceptable energy services to end user. It has in recent years taken attention of policymakers in different parts of the world. Formulating policy to improve energy security is mandatory, not only because of depleting fossil resource, but also implementing diversity of energy source since utilization abundant renewable energy resources can increase the security of energy supply. One of the abundant renewable energy resources in Indonesia is palm oil. This study analyses the utilization of palm biodiesel for Indonesian power generation sector in the Java-Madura-Bali (JAMALI) system. Two scenarios were created by projecting the demand and environmental impact as well as GHG emissions reduction over the next 25 years. The first scenario subjects on current energy policy, while the second scenario is to substitute of fossil fuel which is still used in the JAMALI power generation system. Effect of palm biodiesel on emission of Carbon Dioxide, Carbon Monoxide, Sulfur Dioxide, Nitrogen Oxides, Particulate Matter, and Volatile Organic Compounds were estimated for each scenario. An externality analysis to complete the environmental analysis was conducted and resource analysis of palm oil plantation based biodiesel was also estimated. Finally, the economics feasibility of palm biodiesel in the power generation sector was analyzed.